Study of association of serum bicarbonate levels with mortality in chronic kidney disease - S., Kumar; D., Nikethan (International Journal of Research in Medical Sciences, 2016)
Background: Chronic kidney disease has been recognized as a major global public health problem. The approximate prevalence of CKD in India is 800 per million population. Metabolic acidosis is a feature of CKD due to the reduced capacity of the kidney to synthesise ammonia and excrete hydrogen ions. This may be corrected by oral bicarbonate supplementation or by increasing the bicarbonate concentration in the dialysate fluid during dialysis. Studies have shown that low serum bicarbonate is associated with progression of kidney disease and increased mortality. Due to the limited availability of studies done in Indian population this study was undertaken to assess the serum bicarbonate levels in different stages of CKD and its effect. Methods: Prospective data of 100 patients with various stages of chronic kidney disease admitted and treated in vims hospital in department of medicine and nephrology between January 2014 to June 2015 were studied. Results: out of 100 cases 71 were male and 29 were female. Highest numbers of cases were found in the age group of 51 to 60 years followed by 41 to 50yrs. Most common cause of chronic kidney disease in our study group were diabetes, hypertension, nephrotic syndrome PCKD. Most patients were in stage 4 followed by stage 2, and Many patients had low serum bicarbonate level and only 07 patients had high serum bicarbonate level who were in stage 3 and stage 4. Of the 21 mortality 14 patients had low serum bicarbonate level (10-14 meq/l) and 07 patients had high serum bicarbonate level (mean value 25 meq/l). More death were noticed in the stage 5 followed stage 4 and stage 3 in 6th decade. Out of 100 cases, 68 cases were on dialysis and 32 cases were not on dialysis. Hence present study determines the association of serum bicarbonate levels as a risk factor for mortality in chronic kidney disease. Conclusions: low serum bicarbonate levels are associated with high mortality in chronic kidney disease. Hence it is essential to optimise serum bicarbonates with oral supplementation.